Implementation of Priority Scheduling Algorithm in Designing Infrastructure Damage Reporting System - Kustanto, Prio; Arizky Kurniawan, Wisnu; Noe’man, Achmad; Nurfiyah, Nurfiyah; Ridwan, Ridwan (Greenation International Journal of Engineering Science, 2024)
The rapid growth of population and urbanization in Bekasi District has increased the demand for adequate road infrastructure, but it has also posed challenges in the maintenance and repair of existing infrastructure. The main constraint in addressing this issue is the limited available budget, although the Bekasi District Government has tried various innovative programs. In this context, it is important to have mechanisms that allow the public to report infrastructure problems quickly and accurately. Based on preliminary studies, many factors can cause road infrastructure damage. The aim of this research is to design and develop a Road Infrastructure Damage Complaint System in Bekasi District, providing easy access for the public to report road infrastructure damage and enabling authorities to prioritize infrastructure repairs more quickly and accurately, thus improving the quality of life for the community and building a complaint system that can help expedite the repair process.